2021
DOI: 10.1111/jog.14751
|View full text |Cite
|
Sign up to set email alerts
|

Gene polymorphism associated with TGF‐β1 and susceptibility to preeclampsia: A meta‐analysis and trial sequential analysis

Abstract: Aim Mounts of researches focused on the link between transforming growth factor‐beta 1 (TGF‐β1) polymorphisms and preeclampsia (PE) which is a hypertensive multisystemic disorder affecting pregnancy. However, the results were inconsistent. Thus, a meta‐analysis was performed to obtain more conclusive results. Methods Eligible studies were searched in PubMed, Web of Science, EMBASE, and Scopus. Odds ratios (ORs) with 95% confidence intervals (CIs) were utilized to evaluate the relationship between six TGF‐β1 po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…There are multiple maternal and fetal gene alleles and mutations associated with pre-eclampsia [33][34][35][36][37][38][39] , possibly reflecting the syndromic nature of this disease. Many of these identified genes are associated with thrombophilic factors [34][35][36][37] , angiogenic factors 33,40 or immune responses 38,39 . Fetal trisomy 13 is also associated with increased risk of pre-eclampsia likely due to the extra copy of FLT1 (encoding Fms-related receptor tyrosine kinase 1; FLT1), which is located on chromosome 13 (ref.…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…There are multiple maternal and fetal gene alleles and mutations associated with pre-eclampsia [33][34][35][36][37][38][39] , possibly reflecting the syndromic nature of this disease. Many of these identified genes are associated with thrombophilic factors [34][35][36][37] , angiogenic factors 33,40 or immune responses 38,39 . Fetal trisomy 13 is also associated with increased risk of pre-eclampsia likely due to the extra copy of FLT1 (encoding Fms-related receptor tyrosine kinase 1; FLT1), which is located on chromosome 13 (ref.…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…There are only a few studies utilizing WGCNA in the analysis of genetic predispositions toward preeclampsia. The majority of the studies in this field mainly identify gene polymorphisms in various population groups [ 39 , 40 , 41 , 42 ]. We reiterate that WGCNA might be a more suitable analysis compared to the analysis of differential expression of genes for a broader look into the networks responsible for the pathophysiology of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Gannoun et al investigated genetic polymorphisms in the promoter region of matrix metalloproteinases 9 and 2 (MMP-9 and -2) in a Tunisian Arab population and revealed that the MMP-9 rs3918242 (-562 C > T) variant is related to increased MMP-9 production and is a risk factor for PE [ 90 ]. In a recently published meta-analysis, Liu et al identified transforming growth factor-beta 1(TGF-β1) rs800469 variant as a possible risk factor for PE in Asian population [ 91 ]. TGF-β1 is a cytokine produced during pregnancy by trophoblast cells, involved in the regulation of trophoblast proliferation, differentiation and invasion.…”
Section: Fetal Growth Restriction and Preeclampsia As A Maternal Factormentioning
confidence: 99%